Answer:
Step-by-step explanation:
g(x) = 3x + 5
g(3) = 3(3) + 5
g(3) = 9 + 5
g(3) = 14
-----------------------
f(x) = 2x² + 3
f(g(3)) = 2(g(3)) + 3
f(14) = 2(14²) + 3
f(14) = 2(196) + 3
f(14) = 392 + 3
f(14) = 395
-----------------------------
f(g(3)) = 395
Stan Han Jisung!!!!!He literally cute!!hdbdbdkkdjd
G(x)=− 4 x 2 +7g, left parenthesis, x, right parenthesis, equals, minus, start fraction, x, start superscript, 2, end superscr
steposvetlana [31]
For this case, what we should do is evaluate the function for different points within the range shown.
We then have the following table:
x g(x)
-2 -9
-1 3
0 7
1 3
2 -9
3 -29
4 -57
From where we observed that the average rate of change is:
-13
Answer:
the average rate of change of g over the interval [-2,4] is:
-13
Answer:
3000
Step-by-step explanation:
Answer:
the answer is B. you're welcome